2019
DOI: 10.1038/s41598-019-56206-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and stabilization of the rumen microbiome in yearling Tibetan sheep

Abstract: The productivity of ruminants depends largely on rumen microbiota. However, there are few studies on the age-related succession of rumen microbial communities in grazing lambs. Here, we conducted 16 s rRNA gene sequencing for bacterial identification on rumen fluid samples from 27 Tibetan lambs at nine developmental stages (days (D) 0, 2, 7, 14, 28, 42, 56, 70, and 360, n = 3). We observed that Bacteroidetes and Proteobacteria populations were significantly changed during the growing lambs’ first year of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 40 publications
(40 reference statements)
3
27
0
2
Order By: Relevance
“…Deusch et al [72] reported the high metabolic activity of Verrucomicrobia in the rumen as being due to the higher protein content in comparison to other OTUs; the authors also underlined the minority of this ruminal community and the lack of knowledge regarding its role. It was also reported that the concentrations of these species in the rumen of Tibetan sheep tended to increase with age [73]. Succiniclasticum is a genus of ruminal bacteria that transforms succinate to propionate as the single energy-producing pathway; it also participates in the ruminal metabolism of fatty acids [74].…”
Section: Discussionmentioning
confidence: 99%
“…Deusch et al [72] reported the high metabolic activity of Verrucomicrobia in the rumen as being due to the higher protein content in comparison to other OTUs; the authors also underlined the minority of this ruminal community and the lack of knowledge regarding its role. It was also reported that the concentrations of these species in the rumen of Tibetan sheep tended to increase with age [73]. Succiniclasticum is a genus of ruminal bacteria that transforms succinate to propionate as the single energy-producing pathway; it also participates in the ruminal metabolism of fatty acids [74].…”
Section: Discussionmentioning
confidence: 99%
“…In ruminants, the microbial population is established by successive waves where convergence of microbial populations are seen reaching a more stable population structure 8 11 . The establishment of a gut microbial community is influenced by multiple factors, including diet, environment, and host genotype 2 – 6 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Tibetan sheep (Ovis aries), providing hides, meat, and milk for indigenous Tibetans [13], possessed hypoxia-tolerant and cold-resistant ability in harsh Tibetan plateau [14]. According to the biological function in energy metabolism, ovine SIRT1 and SIRT2 may exert a critical influence on regulation of growth traits in Tibetan sheep.…”
Section: Discussionmentioning
confidence: 99%